Functional Divergence of Microtubule-Associated TPX2 Family Members in Arabidopsis thaliana - Dvořák Tomaštíková, Eva; Rutten, Twan; Dvořák, Petr; Tugai, Alisa; Ptošková, Klara; Petrovská, Beáta; van Damme, Daniel; Houben, Andreas; Doležel, Jaroslav; Demidov, Dmitri (International journal of molecular sciences, 2020)
TPX2 (Targeting Protein for Xklp2) is an evolutionary conserved microtubule-associated protein important for microtubule nucleation and mitotic spindle assembly. The protein was described as an activator of the mitotic kinase Aurora A in humans and the Arabidopsis AURORA1 (AUR1) kinase. In contrast to animal genomes that encode only one TPX2 gene, higher plant genomes encode a family with several TPX2-LIKE gene members (TPXL). TPXL genes of Arabidopsis can be divided into two groups. Group A proteins (TPXL2, 3, 4, and 8) contain Aurora binding and TPX2_importin domains, while group B proteins (TPXL1, 5, 6, and 7) harbor an Xklp2 domain. Canonical TPX2 contains all the above-mentioned domains. We confirmed using in vitro kinase assays that the group A proteins contain a functional Aurora kinase binding domain. Transient expression of Arabidopsis TPX2-like proteins in Nicotiana benthamiana revealed preferential localization to microtubules and nuclei. Co-expression of AUR1 together with TPX2-like proteins changed the localization of AUR1, indicating that these proteins serve as targeting factors for Aurora kinases. Taken together, we visualize the various localizations of the TPX2-LIKE family in Arabidopsis as a proxy to their functional divergence and provide evidence of their role in the targeted regulation of AUR1 kinase activity.
Keywords: proteiny huseníčku; Protein Binding; Microtubule-Associated Proteins; Genes, Plant; Arabidopsis thaliana; Arabidopsis; Amino Acid Sequence; Arabidopsis Proteins; kinase assay; proteiny asociované s mikrotubuly; in vivo co-localization; aurora kinase 1; targeting protein for Xklp2; Microtubules; proteinové domény; vazba proteinů; mikrotubuly; kinasy Aurora; sekvence aminokyselin; phylogeny; rostlinné geny; Aurora Kinases; Protein Domains